Rancangan ruang bermain anak yang kreatif dan edukatif dengan pemanfaatan lahan fasilitas umum - Irnawati Siregar; Zelmi Sriyolja (Dinamika Lingkungan Indonesia, 2020)
The purpose of this study is to plan creative and educative children's play spaces, and to introduce social life at an early age. The problem in this study is that there is no playing environment for children under five and elementary school age, so that it affects the play patterns and creativity of children in their neighborhoods. Children are far from social life, tend to play games using electronic and virtual media. This research method is a qualitative descriptive method, employing surveys in research locations, interviews, observation of children's behavior, and playing patterns. The results of this study are in the form of creative and educative children's play planning by designing play spaces that can interact socially with children of different ages and businesses, as well as revive traditional games of regions that are almost extinct.